Potential of Regional Airport in České Budějovice - Ližbetinová, Lenka; Bartuška, Ladislav; Průša, Petr (EDP Sciences, 2018)
The objective of the contribution is to analyse the potential of the regional airport in České Budějovice after the modernization and obtaining the status of an international public airport in 2020 for the development of the region and inclusion in the category based on its importance. The South Bohemian region is one of the most visited regions in the Czech Republic. To be able to assess the potential considering its popularity among tourists, it is necessary to assess the need for connection of the airport to the transport infrastructure and thus improve its accessibility and comfort. The results published in the contribution are potential basis for further studies and planning of the territorial development of the region.
Potenciál regionálního letiště v Českých Budějovicích
Keywords: Potential; Regional Airport; České Budějovice; Potenciál; regionální letiště; České Budějovice